A note on the Hicksian concept of income - Ajit Zacharias (Levy Economics Institute of Bard College, 2002)
Empirical studies of intertemporal dynamics of individual income, distribution of personal income, and growth and distribution of national income are all based on statistics that rely on some concept of income. The dominant one today appears to be the so-called Haig-Simons-Hicks (HSH) concept of income. I examine the foundations of this concept in Hickss Value and Capital and conclude that there is nothing Hicksian about the HSH concept of income. Furthermore, I argue that Hickss failure to distinguish between definition and calculation, and the consequent lack of adequate ex post concepts, make it impossible for his income definitions to serve as a basis for income accounting.
Keywords: 330